Stereotipes of the National Culture and the “Identity” Problem in the Case of Globalization - Lu. Wang (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article deals with the categories of "stereotype" and "identity" that make up the core of the national culture. The authors proceed from the assumption that the stereotypes that have arisen in the course of historical development create a cliche for the perception of both one's own and another's ethnos, its features and culture. The other side of stereotypes is also noted: at the same time they contribute to the formation of one's own identity. The article shows the features of the formation of cultural stereotypes, their influence on the formation of various aspects of one's own identity in the process of ethnic diversification through the system "own / foreign"). It is justified that the presence of stereotypes can both hamper, and under certain conditions, contribute to the perception of culture as external to this ethnos. The possibility of the existence of multiple identities, formed on different base grounds (territorial, ethnic, confessional, etc.) is proved. It was revealed that during the study of a foreign language it is advisable both to use and to break stereotypes. In the course of the study, it is justified that stereotypes in many respects impede the formation of new identities, especially in the case when the new identity is supranational in nature (as it is assumed in the course of the formation, in particular, of a new "European identity.